Long-term Treatment with Golimumab for Severe Uveitis. (April 2014) - Miserocchi, Elisabetta; Modorati, Giulio; Pontikaki, Irene; Meroni, Pier Luigi; Gerloni, Valeria
Abstract Purpose: To evaluate the long-term efficacy of golimumab in patients with severe recalcitrant uveitis who had inadequate response to previous biologics. Methods: Retrospective study (13 patients with JIA, 4 with HLA-B27-associated uveitis). Indication for treatment was active uveitis despite biologics. Golimumab dosing was 50 mg monthly/subcutaneously. Main outcome measures: uveitis activity, visual acuity improvement, reduction of systemic therapy (corticosteroids/immunosuppressants), adverse events. Results: Of 17 patients (34 affected eyes), response to golimumab was seen in 14 patients; at last visit uveitis was inactive in 12 patients. Three patients were nonresponders. Mean follow-up time on golimumab was 21.9 months. Visual acuity remained stable in 26 eyes, improved in 7, and worsened in 1. Mean systemic prednisolone dose before and after golimumab was 12.5–3.5 mg/day. One patient developed pulmonary infection. Conclusions: Golimumab may be a promising new therapeutic option for severe uveitis patients who have not responded to other biologics.